The impact of copper impregnated wound dressings on surgical site infection following caesarean section: a double blind randomised controlled study. (August 2020) - Arendsen, Linda P.; Thakar, R.; Bassett, P.; Sultan, A.H.
Highlights: Double blinded randomised controlled trial to study the effect of copper impregnated wound dressings on SSI rate following CS. A significant 39% reduction of SSI was observed in the group with the copper wound dressing. No allergic reactions or adverse events were documented with the use of the copper wound dressing. Copper as a natural remedy for the reduction of HCAIs without the use of antibiotics and its risks of antibiotic resistance. Abstract: Objective: To investigate the effect of copper impregnated wound dressings on the surgical site infection (SSI) rate following caesarean section (CS). Design: Single centre double blind randomised controlled trial. Participants: Women aged 18 years or over who had a CS. Interventions: All women were randomised to receive either a copper-oxide impregnated wound dressing (study group) or a non-copper wound dressing (control group). Main outcome measures: The primary study outcome was the incidence of SSI within a 30-day period from CS, assessed via a telephone questionnaire. Secondary outcomes were length of hospital stay, and readmission rate. Results: 324 women were enrolled in the study of whom 159 were randomised to the study group and 165 to the control group. The follow up rate was 97.5%. A total of 78 women (24.1%) developed an SSI within 30 days following CS; 29 (18.2%) in the study group and 49 (29.7%) controls ( P = 0.037, relative risk reduction (RRR) of 38.7%). The incidence of superficial/deep SSI was not significantly different (24.2% vs. 17.6%, P = 0.257), however a significant relative risk reduction of 80.3% for Organ/Space SSI was observed in the study group (12.7% vs. 2.5%, P = 0.002). Length of hospital stay, and readmission rate did not vary significantly between groups. Conclusions: This is the first study to demonstrate a significant reduction in SSI rates following CS with the use of copper impregnated wound dressings. The high SSI rate confirms the importance of new strategies to reduce the infection rate. Copper is a natural remedy which could potentially reduce hospital acquired infections without the use of antibiotics and its associated risks of antibiotic resistance.